2020
DOI: 10.3389/fneur.2020.591615
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative Neurocognitive Function Was More Susceptible to Decline in Isocitrate Dehydrogenase Wild-Type Subgroups of Lower-Grade Glioma Patients

Abstract: Background: Neuropsychological deficits frequently occur in diffuse lower-grade glioma (DLGG) patients, but their relationship with molecular subgroups based on the 2016 World Health Organization (WHO) Classification of Tumors of the Central Nervous System (CNS) is unclear.Methods: All patients enrolled for this study were divided into different subgroups according to the molecular-integrated 2016 CNS WHO and morphology-centric 2007 CNS WHO to compare their neurocognitive function (NCF) dysfunction. Univariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
4
1
Order By: Relevance
“…For abstraction domain, we did not observe any significant improvement during the whole hospitalization and 3-month follow-up. According to Zhang et al, the scores of memory function and abstract thinking were significantly different presented for grade III glioma patients, and their results implied that patients with IDHwt-astrocytoma/anaplastic astrocytoma are more susceptible to suffering from neurocognitive function decline than those with other subgroups of grade II and III gliomas (43). Our current data did not further support the relationship between the cognitive status of MoCA scores and the pathological classification (Supplementary Figures 3-5).…”
Section: Discussioncontrasting
confidence: 83%
“…For abstraction domain, we did not observe any significant improvement during the whole hospitalization and 3-month follow-up. According to Zhang et al, the scores of memory function and abstract thinking were significantly different presented for grade III glioma patients, and their results implied that patients with IDHwt-astrocytoma/anaplastic astrocytoma are more susceptible to suffering from neurocognitive function decline than those with other subgroups of grade II and III gliomas (43). Our current data did not further support the relationship between the cognitive status of MoCA scores and the pathological classification (Supplementary Figures 3-5).…”
Section: Discussioncontrasting
confidence: 83%
“…Emma van Kessel et al found that IDH status is associated with psychomotor speed, memory performance, and executive functioning (van Kessel et al 2022 ). Also, Zhe Zhang et al, summarizing data from a total of 104 patients with primary supratentorial diffuse lower-grade glioma (DLGG), similarly found severe cognitive decline in terms of neurocognitive function performance in patients with IDHwt (Zhang et al 2020 ). To explain this phenomenon, previous studies pointed out that IDH mutations lead to the production of 2-hydroxyglutarate, which is associated with good cognition (Venkatesh et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although this was a cross-sectional study, analyzing the effects of education on MoCA scores longitudinally may provide more insight into cognitive reserve in this patient population. A recent study has found that patients with isocitrate dehydrogenase ( IDH )-wildtype gliomas may have worse cognitive decline than those with IDH -mutant gliomas, 36 and other studies suggest an association between APOE alleles and cognitive function among brain tumor patients. 37 This suggests further genomic analysis in addition to neurocognitive testing may be necessary to understand the patient’s overall cognitive profile and provide appropriate treatment.…”
Section: Discussionmentioning
confidence: 99%